Cenomanian/Turonian benthic foraminiferal faunas of the Demerara Rise depth transect (ODP Leg 207) - Friedrich, Oliver; Erbacher, Jochen; Mutterlose, J¶rg (Anuário do Instituto de Geociências, 2006)
Abstract